Strenghthening Digital Literacy of Elementary School Students Through Utilization of Wordwall as Game-Based Learning Interactive Media - Fitri Hamidah; Fajar Setiawan; Lilik Binti Mirnawati (Universitas Pendidikan Ganesha, 2023)
The lack of innovative learning media impacts students' diminishing abilities. Besides that, other problems were also found in students' needing more digital literacy. This study aims to create the use of word walls as an interactive media game-based learning to strengthen digital literacy, especially for elementary school students. This type of research is qualitative research. The research method in this study is a qualitative method with a descriptive approach. The research subjects of upper-class students (grade V) totaling 20 people. Methods of data collection using observation, interviews, and documentation. The data collection instrument used a questionnaire. The data analysis technique uses qualitative descriptive analysis. The research results are that students are enthusiastic about participating in class so that learning becomes more enjoyable compared to conventional learning, and students do not feel bored when learning occurs. Based on digital literacy skills, it is known that students are capable and proficient in operating digital technology word wall templates chasing in mazes, and matching games from the beginning to the end of the game. Using word walls can strengthen digital literacy for elementary school students. This study concludes that using word walls is a new thing that can arouse students' enthusiasm in learning.